2021
DOI: 10.1111/febs.16025
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3G rescues cells from the deleterious effects of DNA damage

Abstract: Human apolipoprotein B mRNA editing enzyme, catalytic polypeptide‐like 3G (hA3G), a member of the APOBEC family, was described as an anti‐HIV‐1 restriction factor, deaminating reverse transcripts of the HIV‐1 genome. Several types of cancer cells that express high levels of A3G, such as diffuse large B‐cell lymphoma cells and glioblastomas, show enhanced cell survival after ionizing radiation and chemotherapy treatments. Previously, we showed that hA3G promotes (DNA) double‐strand breaks repair in cultured cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…1A, right panel). These results indicate that recombinant A3G as well as the endogenous A3G expressed in lymphoma cells promotes DSB repair, supporting our previous reports [39,43,45].…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1A, right panel). These results indicate that recombinant A3G as well as the endogenous A3G expressed in lymphoma cells promotes DSB repair, supporting our previous reports [39,43,45].…”
Section: Resultssupporting
confidence: 92%
“…This notion is supported by: (a) in vitro experiments showing that in the presence of A3G, Klenow fragment DNA polymerase accomplishes the synthesis of both DNA strands containing minimal homology of two bases [39,61]; (b) A3G undergoes intersegmental transfer [56,62], allowing it to directly juxtapose two ssDNA termini with minimal terminal microhomology leading to error‐free NHEJ and if juxtaposes along the resected ssDNA it will generate error prone‐NHEJ. Others and we showed that A3G, albeit its predominant cytoplasmic protein, can translocate, reside and act in the nuclei [25,39,45,63–66] pointing at its potential to interact with damaged DNA in the cell genome.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most A3 proteins are found throughout the cell (19) and all A3s except A3A have been previously associated with ribonucleoprotein complexes in the cytoplasm, which is consistent with our PPI dataset (14, 5154). Additionally, although A3D and A3G were thought to be only cytoplasmic, several more recent reports have shown that they are also found in the nucleus (46, 55, 56). Only A3B has a nuclear localization signal that places the majority of A3B in a single compartment, but similar to other A3s, there are conditions where it becomes relocalized to the cytoplasm (53, 57).…”
Section: Resultsmentioning
confidence: 99%
“…Most A3 proteins are found throughout the cell ( 19 ), and all A3s except A3A have been previously associated with ribonucleoprotein complexes in the cytoplasm, which is consistent with our PPI dataset ( 14 , 51 , 52 , 53 , 54 ). Additionally, although A3D and A3G were thought to be only cytoplasmic, several more recent reports have shown that they are also found in the nucleus ( 46 , 55 , 56 ). Only A3B has a nuclear localization signal that places the majority of A3B in a single compartment, but similar to other A3s, there are conditions where it becomes relocalized to the cytoplasm ( 53 , 57 ).…”
Section: Resultsmentioning
confidence: 99%